2014
DOI: 10.1016/j.jbiotec.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on refolding of recombinant pentameric cholera toxin B

Abstract: The production of recombinant proteins is an essential tool for the expansion of modern biological research and biotechnology. The expression of heterologous proteins in Escherichia coli often results in an incomplete folding process that leads to the accumulation of inclusion bodies (IB), aggregates that hold a certain degree of native-like secondary structure. High hydrostatic pressure (HHP) impairs intermolecular hydrophobic and electrostatic interactions, leading to dissociation of aggregates under non-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Mild refolding conditions involving the use of detergents [ 12 ], reversed micelles, and an intermediate or low concentration of denaturant [ 60 ] as well as physical conditions such as alkaline pH and/or high hydrostatic pressure have been reported [ 16 , 21 , 22 , 61 ] as strategies for high yields. HHP refolding has particularly been used successfully to refold several proteins including an oligomeric [ 17 ] as well as a disulphide rich protein [ 15 ] both of which demonstrated reasonably high yields of well folded protein. Such yields are obtainable since solubilization takes place without disrupting hydrogen bonds that maintain their secondary structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild refolding conditions involving the use of detergents [ 12 ], reversed micelles, and an intermediate or low concentration of denaturant [ 60 ] as well as physical conditions such as alkaline pH and/or high hydrostatic pressure have been reported [ 16 , 21 , 22 , 61 ] as strategies for high yields. HHP refolding has particularly been used successfully to refold several proteins including an oligomeric [ 17 ] as well as a disulphide rich protein [ 15 ] both of which demonstrated reasonably high yields of well folded protein. Such yields are obtainable since solubilization takes place without disrupting hydrogen bonds that maintain their secondary structure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, proteins with reduced cysteines are highly prone to aggregation which arise as a result of irreversible mispairing of free cysteines during refolding [15]. In order to circumvent the problem of aggregation and protein loss, the use of high hydrostatic pressure (HHP) has been applied in solubilizing and refolding of some IBs [15][16][17][18][19][20]. HHP in the range of 1-3 kbar for about 90 mins, in combination with mild concentrations of chaotropes or alkaline pH have been reported to enhance dissociation of oligomers and disaggregation of intermolecular hydrophobic and electrostatic interactions [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Several previously published works have considered the mechanical strain response of the cells in response to hydrostatic pressure. [20][21][22][23][24] In most of these studies, the cellular viability, cytoskeletal reorganization, or proliferation was observed or characterized. Nerem was one of the first researchers who designed an experiment inspired by physiological blood flow inside vessels to investigate the effect of developed flow on the shape, orientation, and reorganization of F-actin structures.…”
Section: Introductionmentioning
confidence: 99%
“…A técnica tem se mostrado eficiente para a renaturação de diversas proteínas (FRAGA et al, 2010;MALAVASI et al, 2011;ZHENG et al, 2013;RODRIGUES et al, 2014;LEMKE et al, 2015) e, portanto, ela foi empregada na tentativa de renaturar as porções da proteína LepA388. Após diferentes condições para a renaturação, o tratamento com o tampão composto por 50 mM Tris-EDTA pH 8,0 e 500 mM de L-arginina pH 11,0 foi o mais eficiente para que a maior concentração das proteínas estivesse na fração solúvel (Figura 33 e Figura A6 da seção Apêndices).…”
Section: Discussionunclassified